MDR1 Gene Polymorphisms and Its Association With Expression as a Clinical Relevance in Terms of Response to Chemotherapy and Prognosis in Ovarian Cancer - Haque, Absarul; Sait, Khalid Hussain Wali; Alam, Qamre; Alam, Mohammad Zubair; Anfinan, Nisreen; Wali, Abdul Wahab Noor; Rasool, Mahmood (Frontiers in Genetics, 2020)
In spite of the significant advancements in the treatment modalities, 30% of advanced stage ovarian cancer (OC) patients do not respond to the standard chemotherapeutic regimen and most of the responders finally relapse over time due to the escalation of multidrug resistance (MDR) Phenomenon. Our present study evaluated chemotherapeutic sensitivity response among 47 ovarian tumor patients of which we found 37 (78.8%) sensitive and remaining 10 (21.2%) resistant. Among the resistant, seven tumor samples were found to be platinum resistant or refractory to platinum (CB/TX), one to carboplatin, and two to 5FU. Notably, all these resistant cases were observed in the disease recurrence group of patients identified at stage III or IV. The stage III resistant cases revealed heterozygous mutation (C/T) in exon 12 (C1236T) and 26 (C3435T) and increased level of mRNA, whereas homozygous mutation (T/T) was found at stage IV tumor patients. The genotypic difference was found to be significant (p = 0.03) for exon 12, and p = 0.003 for exon 26 mutant genotypes. No significant association between genotypes of different exons with tumor stages and tumor grade was observed (p > 0.05). However, a significant association was observed between the genotype of exon-12 and histopathology of tumor tissue (p = 0.028). Statistically, the chemotherapy response was found to be significantly associated with the tumor stage (p = 0.019). We also observed a significant difference in PFS (P = 0.019) and OS (P = 0.047) between tumor grades 1 and 3. Notably, the highest mRNA expression was observed in resistant tumor sample T-32, where interestingly we found homozygosity TT in all of the exons 12, 21, and 26. Thus, we suggest that exons 12 (C1236T) and exon 26 (C3435T) polymorphism may play a role in inducing drug resistance by altering the expression level of the MDR1 gene. To summarize, we suggest that the expression of MDR1 in OC is influenced by tumor stage and genotype variants as well as by chemotherapeutic drugs. Thus our findings suggest that inter individual variability in platinum based therapy may be anticipated by MDR1 genotypes. Further studies on a large number of samples shall eventually lead to provide beneficial information for the individualized chemotherapy.